2020
DOI: 10.26905/enjourme.v5i1.4228
|View full text |Cite
|
Sign up to set email alerts
|

First experiences in a school-based practicum: Pre-service teachers’ emotion and perceived benefits towards the program

Abstract: School-based practicum is an inseparable part of Indonesian teacher education. The aim of the present study is to explore initial experiences of pre-service English teachers (PSETs) on a school-based practicum program. Under a qualitative case study, four first-year PSETs of a private university in Yogyakarta, Indonesia were purposefully selected as the participants. Data were collected through semi-structured interview, the handbook of the program, and the PSETs' reflective journals. The results suggested tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 10 publications
(37 reference statements)
0
13
0
Order By: Relevance
“…As reported in the literature (for example Derosa 2016;Alexander, 2018;Gravette & Jiyane, 2019;Lestari, 2020), it is not uncommon to find novice teachers expressing mixed feelings as they encounter real life classrooms. Some of the expressions showcase confidence based on the ability to deliver lessons in the classroom.…”
Section: Issues Related To School Environment/postingmentioning
confidence: 91%
See 2 more Smart Citations
“…As reported in the literature (for example Derosa 2016;Alexander, 2018;Gravette & Jiyane, 2019;Lestari, 2020), it is not uncommon to find novice teachers expressing mixed feelings as they encounter real life classrooms. Some of the expressions showcase confidence based on the ability to deliver lessons in the classroom.…”
Section: Issues Related To School Environment/postingmentioning
confidence: 91%
“…Despite the benefits discussed above, researchers (for example Pham et al, 2020;Lestari, 2020) have pointed to some serious shortcomings of teaching practicum. Pham et al (2020) found "inadequate duration and inappropriate timing" (p.29) to have impeded newly qualified teachers' capacity to enjoy a positive experience.…”
Section: Shortcomings Of Teaching Practicum As a Component Of Itementioning
confidence: 99%
See 1 more Smart Citation
“…From a researcher's point of view, it is very common to take samples from a teacher's diary or reflective journal to find out the level of happiness experienced by an English teacher (Frenzel, 2014;Lestari, 2020). The profession of a teacher is a very noble ideal and is different from other professions.…”
Section: Alvian and Mbatomentioning
confidence: 99%
“…In addition, anger has often been experienced by English teachers in studies that explored the different frequencies and emotional experiences among teachers of learning in a foreign language classroom (Ghanizadeh & Royaei, 2015;Lestari, 2020;H. Li, 2020;Liu, 2016).…”
Section: Alvian and Mbatomentioning
confidence: 99%